CLINICAL CLASSIFICATION OF TUBERCULOSIS WHEN ASSESSING THE PREVALENCE OF CAVERNOUS FORMS OF THE DISEASE - I. P. Solovieva; Ya. V. Lazareva; Yu. S. Berezovskiy (Туберкулез и болезни лёгких)
Cavernous form of tuberculosis being important in its clinical aspects is presented with the reference to pathogenesis, morphogenesis, structure of cavitary wall as acute pneumoniogenic cavity, bronchogenic cavity, cavity from the focus with pre-existing capsule, without expressed fibrosis, with perifocal changes and without them, with semination foci and without them.The statement of the long-lasting impropriety of official statistic rates received through current clinical classification of tuberculosis (ICD-10) explains the increase oftuberculosis prevalence and raises the need to review the classification oftuberculosis and points atthe urgency oftuberculosis control actions adequate for current unfavorable epidemic situation.